2020
DOI: 10.3390/ijms21207467
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mitochondrial Membrane Potential Identify Distinct Populations of Human Cardiac Mesenchymal Progenitor Cells

Abstract: Adult human cardiac mesenchymal progenitor cells (hCmPC) are multipotent resident populations involved in cardiac homeostasis and heart repair. Even if the mechanisms have not yet been fully elucidated, the stem cell differentiation is guided by the mitochondrial metabolism; however, mitochondrial approaches to identify hCmPC with enhanced stemness and/or differentiation capability for cellular therapy are not established. Here we demonstrated that hCmPCs sorted for low and high mitochondrial membrane potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…On the other hand, incubation of cells with all OCP-Sr for 96 h did not lead to an increase in the content of acidic compartments in the cells (Figure 6b). Additionally, to verify flow cytometry data, the content of acidic compartments and mitochondrial membrane potential in C3H/10T1/2 cells were examined using confocal microscopy after 96 h of co-incubation with OCP and OCP-Sr. For this, cells were stained Additionally, to verify flow cytometry data, the content of acidic compartments and mitochondrial membrane potential in C 3 H/10T1/2 cells were examined using confocal microscopy after 96 h of co-incubation with OCP and OCP-Sr. For this, cells were stained with LysoTracker Green and MitoTracker Red CMXRos [29]. H33342 was used to visualize the cell nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, incubation of cells with all OCP-Sr for 96 h did not lead to an increase in the content of acidic compartments in the cells (Figure 6b). Additionally, to verify flow cytometry data, the content of acidic compartments and mitochondrial membrane potential in C3H/10T1/2 cells were examined using confocal microscopy after 96 h of co-incubation with OCP and OCP-Sr. For this, cells were stained Additionally, to verify flow cytometry data, the content of acidic compartments and mitochondrial membrane potential in C 3 H/10T1/2 cells were examined using confocal microscopy after 96 h of co-incubation with OCP and OCP-Sr. For this, cells were stained with LysoTracker Green and MitoTracker Red CMXRos [29]. H33342 was used to visualize the cell nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…with LysoTracker Green and MitoTracker Red CMXRos [29]. H33342 was used to visualize the cell nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 K ). TMRM high cells have been shown to be efficient in terms of oxygen consumption rate (OCR), basal and maximal respiration, and spare respiratory capacity compared with TMRM low cells ( Choi et al, 2018 ; Franco-Iborra and Tanji, 2020 ; Gambini et al, 2020 ). In line with this, inhibition or depletion of PLD2 in brown adipocytes significantly enhanced the rate of oxygen consumption and the degree of oligomycin insensitive respiration ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also observed discrepancies in MitoTracker intensity across different cell populations under the same conditions (Figure 3). It has previously been shown that the degree of MitoTracker intensity is associated with distinct metabolic phenotypes within the same cell population [58]. This may be particularly true for cell populations that are undergoing dynamic metabolic remodeling in response to mild mitochondrial stress.…”
Section: Discussionmentioning
confidence: 99%